Research on Rapid Detection of Salmonella and Listeria monocytogenes Using Colloidal Gold Immunoassay and PCR Methods - Fu, Guoqiang; Ning, Zhesheng; Wang, Enxu (International Journal of Public Health and Medical Research, 2024)
This study used colloidal gold immunoassay strips and PCR (probe method) kit methods to detect Salmonella and Listeria monocytogenes. The accuracy and precision of the colloidal gold immunoassay strips and PCR (probe method) kit methods were validated using proficiency testing blind samples, and the consistency with the current national gold standard method was compared. The results of the two rapid detection methods were consistent with the results of the national standard method. This paper also analyzed the detection time and cost of the two rapid detection methods and the national standard method. The PCR (probe method) kit method takes less time for detection and can be used for high-throughput detection, with high sensitivity and low interference. It requires high equipment and personnel capabilities. The colloidal gold immunoassay strips method has the lowest detection cost, but its sensitivity is lower than that of the PCR method. It is easy to operate and requires low personnel and equipment requirements. Laboratories can choose the appropriate method based on their actual needs.